DOA estimation method for sparse arrays based on deep convolutional autoencoder and deep convolutional neural network - Guo, Shuhan; Zhang, Qin; Fu, Xiaolong; Zheng, Guimei; Zhou, Hao (Digital signal processing, 2026)
This paper proposes a Direction-of-Arrival (DOA) estimation method based on Deep Convolutional Autoencoder (DCAE). This method constructs a DCAE to map the covariance matrix of the received signals of a sparse array into a feature space and then reconstructs it into the covariance matrix of the received signals of a uniform linear array. Subsequently, the DOA estimation is performed in combination with the MUSIC algorithm, which effectively increases the degrees of freedom of the sparse array and better solves the DOA estimation problem under the underdetermined condition of the sparse array. To address the issues of low estimation accuracy and poor angular resolution in traditional algorithms for sparse arrays, a DOA estimation method based on Deep Convolutional Neural Network (DCNN) is proposed. This method extracts the mapping from the covariance matrix of the received signals of the physical elements of the sparse array to the angles of arrival, achieving higher accuracy and higher resolution DOA estimation.